Orangutan diaries [videorecording (DVD)] : saving our closest relatives - Leonard, Steve; Drøscher-Nielsen, Lone, 1964-; Strachan, Michaela, 1966- (PBS, 2012)
Follows the work of Lone Drøscher-Nielsen and the Borneo Orangutan Survival Foundation deep in the Borneo rainforest, where a dedicated team of vets and carers have rescued 600 orangutans, many of them orphaned. Their task is to return the animals to health, teach them how to live in the jungle, and return them to their homes, a task that can take several years for each individual.